Foldscope as a diagnostic tool for identification of parasites of domesticated animals - BAL, MANDEEP SINGH; SAGAR, RASHMI; KAUR, PARAMJIT; MAHAJAN, V; SINGLA, L D; SINGH, C K (The Indian Journal of Animal Sciences, 2019)
The present study was carried out to evaluate the effectiveness of foldscope (portable paper microscope) attached with smartphone as a novel, valuable low cost tool for quick diagnosis of animal parasitic diseases under field condition so as to manage the infection at an early stage. To fulfil the objective of the study, specimens of ectoparasites, helminth parasites, haemoparasites, faecal and skin scrapings from animals/clinical cases were examined by foldscope and pictures were taken. All the parasitic slides were also examined by conventional light microscope for comparison purpose and to validate the results. From the results it was observed that foldscope (with magnification of 140Ã—) can be used as a cheap, effective and reliable diagnostic tool to identify helminth and arthropod parasites with comparable efficacy to that of expensive light microscope. Faecal samples with heavy infection of parasitic eggs/ ova/cysts and Trypanosoma evansi were detectable by foldscope with comparable efficacy with optical microscope. However, low grade gastrointestinal parasitic infections and intracellular haemoparasites were not detected using foldscope. This is the first report on evaluation of diagnostic efficacy of foldoscope to detect economically important parasitic infections of livestock and companion animals in India and its field application. Mobile phone enabled imaging and diagnostics technologies have the potential to bring revolutionary changes in the field of animal disease diagnosis.